Herd Immunity Likely Protected the Men Who Have Sex With Men in the Recent Hepatitis A Outbreak in San Diego, California. (25th July 2018) - Smith, Davey; Huynh, Christina; Moore, Adam J; Frick, Andrew; Anderson, Christy; Porrachia, Magali; Scott, Brianna; Stous, Sarah; Schooley, Robert; Little, Susan; Santos, AsherLev T
Abstract: A high seroprevalence of hepatitis A virus (81%) among human immunodeficiency virus–negative high-risk men who have sex with men is likely why this community was largely spared from a recent hepatitis A virus outbreak in San Diego, California.